The association between albuminuria and arterial stiffness in a rural population from Northern China - Bao Shu-min; Huang Wen; Yang Jin-gang; Liang Qiao-jing; Liang Yuan-bo; Wang Ning-li; Zhang Guo-juan (Linchuang shenzangbing zazhi)
ObjectiveTo investigate the association between albuminuria and arterial stiffness in a rural population from Northern China.MethodsUsing a stratified cluster multi-stage sampling method， residents over 30 years old from 13 villages in Yongnian County， Handan City， Hebei Province， China from October 1， 2006， to October 1， 2007 were selected. Finally， 3694 subjects were enrolled in the cross-sectional study. They were divided into the albuminuria group and non-albuminuria group according to the urinary albumin-to-creatinine ratio（ACR）. Brachial-ankle pulse wave velocity （baPWV） and other 19 factors were compared between the two groups. The subjects were then divided into four groups based on the baPWV values，and albuminuria and other 19 factors were compared among the four groups. Multivariate logistic regression analysis was used to evaluate the association between albuminuria and baPWV.ResultsBaPWV ［（1689.44 ± 430.60）cm/s vs （1556.49 ± 347.48）cm/s］， age ［（54.56 ± 10.49）years vs （50.96 ± 10.80）years］， female proportion （60.2% vs 53.4%）， systolic blood pressure ［（146.61 ± 24.10）mmHg vs （137.99 ± 20.98）mmHg， 1 mmHg=0.133 kPa］， diastolic blood pressure ［（80.28 ± 12.93）mmHg vs （77.37 ± 11.89）mmHg］， mean arterial pressure［（102.39 ± 15.07）mmHg vs （97.58 ± 13.61）mmHg］， pulse ［（66.34 ± 18.72）beats/min vs （60.62 ± 15.85）beats/min］， waist-to-hip ratio ［（0.91 ± 0.05）vs （0.90 ± 0.05）］， hypersensitivity C-reactive protein ［（1.05 ± 0.41）mg/L vs （0.82 ± 0.37）mg/L］， total cholesterol ［（4.80 ± 1.0）mmol/L vs （4.59 ± 0.94）mmol/L］， low-density lipoprotein ［（2.84 ± 0.66）mmol/L vs （2.70 ± 0.65）mmol/L］， and triacylglycerol ［（1.65 ± 1.26）mmol/L vs （1.50 ± 1.04）mmol/L］ were significantly higher in the albuminuria group than those of the non-albuminuria group （all P<0.05）， while the estimated glomerular filtration rate （eGFR） ［90.95（81.37，99.54）mL·min-1·（1.73 m2）-1 vs 92.51（84.06，101.53）mL·min-1·（1.73 m2）-1］ was significantly lower in the albuminuria group （P=0.002）. More subjects in the albuminuria group suffered from hypertension （62.1% vs 47.0%， P<0.001） or diabetes （10.7% vs 5.6%， P<0.001）. The increase in baPWV was associated with the increase in ACR and the decrease in eGFR. Multivariate Logistic regression analysis showed that age， diabetes， blood creatinine， hypertension and baPWV were independent risk factors for elevated ACR， and the corresponding odds ratios （95% CI） were 1.018 （1.008-1.028）， 1.348 （1.094-1.660）， 1.548 （1.137-2.107）， 0.986 （0.978-0.004） and 1.0004 （1.000-1.001）， respectively.ConclusionIn the general population， there is a significant correlation between albuminuria and baPWV.